2018
DOI: 10.1172/jci95993
|View full text |Cite
|
Sign up to set email alerts
|

Human CD30+ B cells represent a unique subset related to Hodgkin lymphoma cells

Abstract: Very few B cells in germinal centers (GCs) and extrafollicular (EF) regions of lymph nodes express CD30. Their specific features and relationship to CD30-expressing Hodgkin and Reed/Sternberg (HRS) cells of Hodgkin lymphoma are unclear but highly relevant, because numerous patients with lymphoma are currently treated with an anti-CD30 immunotoxin. We performed a comprehensive analysis of human CD30+ B cells. Phenotypic and IgV gene analyses indicated that CD30+ GC B lymphocytes represent typical GC B cells, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 68 publications
(94 reference statements)
5
43
1
1
Order By: Relevance
“…However, until recently, the cell of origin of HRS cells in HL was not clear. A recent study by Weniger et al showed that the transcriptomic profile of HRS cells is highly similar to that of CD30 + B cells, a rare B cell subset inside germinal centers (Weniger et al, 2018). In the same study, the transcriptional differences between the CD30 + B cell subset and HRS cells of HL were compared, and this showed significant downregulation of genomic stability regulators and cytokinesis.…”
Section: Introductionmentioning
confidence: 92%
“…However, until recently, the cell of origin of HRS cells in HL was not clear. A recent study by Weniger et al showed that the transcriptomic profile of HRS cells is highly similar to that of CD30 + B cells, a rare B cell subset inside germinal centers (Weniger et al, 2018). In the same study, the transcriptional differences between the CD30 + B cell subset and HRS cells of HL were compared, and this showed significant downregulation of genomic stability regulators and cytokinesis.…”
Section: Introductionmentioning
confidence: 92%
“…[1][2][3] HRS cells are derived from crippled, largely CD30 1 , pre-apoptotic germinal center (GC) B cells that lack functional B-cell receptors (BCRs) and have reduced expression of multiple B-cell transcription factors. 1,4 These tumor cells rely on alternative signaling and survival pathways, including JAK/STAT and nuclear factor kB (NF-kB), and exhibit genetic alterations of select pathway components. 1,[5][6][7][8][9][10] In 30% to 40% of cHLs in North America and Europe, the malignant HRS cells have evidence of latent Epstein-Barr virus (EBV) infection and associated expression of latent membrane protein 1 (LMP1) and latent membrane protein 2A (LMP2A).…”
Section: Introductionmentioning
confidence: 99%
“…Small numbers of human tonsillar mononuclear cells are CD30 + B cells. These cells appear to be a subpopulation of B cells that develop during normal germinal center reactions in lymphoid tissue, and share some transcriptional patterns with Hodgkin lymphoma cells ( 43 ). In non-B cell systems, CD30 can bind TRAFs 1, 2, and 3 ( 44 , 45 ).…”
Section: Interactions Between Traf3 the B Cell Antigen Receptor (Bcrmentioning
confidence: 99%